Tornado In The Sea: A Media Transposition of the Barracuda Series Painting into a Musical Composition - Rama Anggara; Asril Asril (Universitas Negeri Medan, 2023)
This work is the manifestation of the transformation of Zaimie bin Sahibil’s painting, Barracuda Series, into musical form. The Barracuda Series painting presents the beauty and richness of the ocean bed as a utopian paradigm of the maritime ecology of the coastal community of Sabah, Malaysia. The composer was inspired by his own aesthetic experience when appreciating the painting. This aesthetic experience became the material object that was treated with the concept of media transposition and turned into a musical composition. The media transposition was implemented through the interpretation and transformation of the external and internal structural levels of the Barracuda Series painting. These elements were adapted to create musical elements as a form of innovation in the way the composition was created. the creation of this work involved a number of work stages that were implemented constructively through a method of creation. These stages included: an analysis of data sources, experimentation, contemplation, composition, and formation. The work process utilized the results of extra-aesthetic interpretation and intra-aesthetic transformation to create an innovative musical text. The musical composition Tornado in the Sea uses the instrumentation of piano, violin, and kalimba. The stages of creation included an analysis of data sources, experimentation, contemplation, arrangement, formation, and execution.